Evaluation of different insecticides for the control of giant borer (Telchin licus) eggs in sugarcane crop (International Seven Journal of Multidisciplinary, 2024)
In Brazil, one of the pests responsible for significant losses in sugarcane crops is the giant borer, with a higher incidence in the North and Northeast regions, but it has already been evidenced in the Southeast. Even though the region is the first in the country to produce sugarcane on a large scale, its occurrence is recent. However, this pest has an endophytic habit, that is, it feeds on the stalk, opening ascending galleries in its larval and pupal period, remaining for two to ten months at this stage, making it difficult to manage assertively to control this caterpillar. Thus, this work proposes new means to combat the pest, evaluating different insecticides to control moth eggs, as this stage is one of the only times when the pest is unprotected in the clumps of sugarcane.